2014
DOI: 10.1017/jfm.2014.449
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional dynamics of a turbulent axisymmetric wake

Abstract: The coherent structures of a turbulent wake generated behind a bluff three-dimensional axisymmetric body are investigated experimentally at a diameter based Reynolds number ∼ 2×10 5 . Proper orthogonal decomposition of base pressure measurements indicates that the most energetic coherent structures retain the structure of the symmetry-breaking laminar instabilities and manifest as unsteady vortex shedding with azimuthal wavenumber m = ±1. In a rotating reference frame, the shedding preserves the reflectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
144
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(183 citation statements)
references
References 18 publications
36
144
3
Order By: Relevance
“…Figure 5 compares the premultiplied spectral density for the unforced and forced flows, the latter at maximum pressure recovery, C µ = 0.04 and St θ = 0.107. The unforced spectral density at this radius is qualitatively similar to the radially averaged result presented in figure 3 of Rigas et al (2014b). Within the pressure recovery regime, the effect of high-frequency forcing on pressure fluctuations is a broadband suppression occuring across all modes, without any obvious mode selection.…”
Section: Mean Velocitysupporting
confidence: 79%
See 3 more Smart Citations
“…Figure 5 compares the premultiplied spectral density for the unforced and forced flows, the latter at maximum pressure recovery, C µ = 0.04 and St θ = 0.107. The unforced spectral density at this radius is qualitatively similar to the radially averaged result presented in figure 3 of Rigas et al (2014b). Within the pressure recovery regime, the effect of high-frequency forcing on pressure fluctuations is a broadband suppression occuring across all modes, without any obvious mode selection.…”
Section: Mean Velocitysupporting
confidence: 79%
“…A full description of the unforced wake in the present experiment is provided by Rigas et al (2014b) who show that the coherent structures of the turbulent wake retain the symmetry-breaking properties of the laminar wake. Similarly, oscillatory bifurcations appearing at low Reynolds numbers (the ones at higher Reynolds numbers breaking reflectional symmetry) also appear in the turbulent wake as axisymmetric "bubble pumping" (Berger et al 1990) and as "vortex shedding" (Achenbach 1974;Taneda 1978;Fuchs et al 1979;Berger et al 1990), a large-scale anti-symmetric oscillation.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such anti-symmetric oscillations have been later found to be a major feature of the wake of other more complex configurations such as truncated cylinders with afterbody. 6,7 In a recent investigation, Rigas et al 8 experimentally characterized the unsteady base pressure field of an axisymmetric truncated model. Based on the analysis of the base flow pressure dynamics, the authors identified a second, yet important very-low frequency contribution of the anti-symmetric m = 1 mode, possibly associated with a rotation of the shedding plane and corresponding instantaneous offset of the base pressure centroid.…”
Section: Introductionmentioning
confidence: 99%